Cover Image, Volume 57, Number 4, April 2022. Issue 4 (28th March 2022) - Gipsman, Alexander; Prero, Moshe; Toltzis, Philip; Craven, Daniel
Abstract : Front Cover Caption : The cover image is based on the Review Tracheobronchitis in children with tracheostomy tubes: Overview of a challenging problem by Alexander Gipsman et al., https://doi.org/10.1002/ppul.25814 . [Correction added on 26 March 2022, after first online publication: This additional cover was added to the issue.]